Ecosystem services provision by Mediterranean forests will be compromised above 2℃ warming. (6th July 2021) - Morán‐Ordóñez, Alejandra; Ramsauer, Julia; Coll, Lluis; Brotons, Lluís; Ameztegui, Aitor
Abstract: Forests provide a wide range of provisioning, regulating and cultural services of great value to societies across the Mediterranean basin. In this study, we reviewed the scientific literature of the last 30 years to quantify the magnitude of projected changes in ecosystem services provision by Mediterranean forests under IPCC climate change scenarios. We classified the scenarios according to the temperature threshold of 2℃ set by the Paris Agreement (below or above). The review of 78 studies shows that climate change will lead to a general reduction in the provision of regulating services (e.g. carbon storage, regulation of freshwater quantity and quality) and a general increase in the number of fires, burnt areas and generally, an increase in climate‐related forest hazards (median + 62% by 2100). Studies using scenarios above the 2℃ threshold projected significantly more negative changes in regulating services than studies using scenarios below this threshold. Main projected trend changes on material services (e.g. wood products), were less clear and depended on (i) whether or not the studies considered the interaction between the rise in temperatures and other drivers (e.g. forest management, CO2 fertilization) and (ii) differences in productivity responses across the tree species evaluated. Overall, the reviewed studies projected significant reductions in range extent and habitat suitability for the most drought‐sensitive forest species (e.g. −88% Fagus sylvatica ), while the amount of habitat available for more drought‐tolerant species will remain stable or increase; however, the magnitude of projected change for these more xeric species was limited when high‐end extreme climatic scenarios were considered (above Paris Agreement). Our review highlights the benefits that climate change mitigation (to keep global mean temperature increase <2℃) can bring in terms of service provision and conservation of Mediterranean forests. Abstract : The review of 78 studies shows that climate change will lead to a general reduction in the provision of regulating services by Mediterranean forests (e.g. carbon storage) and a general increase in fires and other climate‐related forest hazards (median + 62% by 2100). Studies using scenarios above the 2℃ Paris Agreement threshold projected significantly more negative changes in regulating services than studies using scenarios below this threshold. Range extent and habitat suitability for the most drought‐sensitive forest species will decrease (e.g. −88% Fagus sylvatica ), while the amount of habitat available for more drought‐tolerant species will remain stable or increase.